Performance and alertness effects of caffeine, dextroamphetamine, and modafinil during sleep deprivation - WESENSTEN, NANCY J.; KILLGORE, WILLIAM D. S.; BALKIN, THOMAS J. (Journal of sleep research, 2005)
Summary Stimulants may provide short‐term performance and alertness enhancement during sleep loss. Caffeine 600 mg, d‐amphetamine 20 mg, and modafinil 400 mg were compared during 85 h of total sleep deprivation to determine the extent to which the three agents restored performance on simple psychomotor tasks, objective alertness and tasks of executive functions. Forty‐eight healthy young adults remained awake for 85 h. Performance and alertness tests were administered bi‐hourly from 8:00 hours day 2 to 19:00 hours day 5. At 23:50 hours on day 4 (after 64 h awake), subjects ingested placebo, caffeine 600 mg, dextroamphetamine 20 mg, or modafinil 400 mg (n = 12 per group). Performance and alertness testing continued, and probe tasks of executive function were administered intermittently until the recovery sleep period (20:00 hours day 5 to 8:00 hours day 5). Bi‐hourly postrecovery sleep testing occurred from 10:00 hours to 16:00 hours day 6. All three agents improved psychomotor vigilance speed and objectively measured alertness relative to placebo. Drugs did not affect recovery sleep, and postrecovery sleep performance for all drug groups was at presleep deprivation levels. Effects on executive function tasks were mixed, with improvement on some tasks with caffeine and modafinil, and apparent decrements with dextroamphetamine on others. At the doses tested, caffeine, dextroamphetamine, and modafinil are equally effective for approximately 2–4 h in restoring simple psychomotor performance and objective alertness. The duration of these benefits vary in accordance with the different elimination rates of the drugs. Whether caffeine, dextroamphetamine, and modafinil differentially restore executive functions during sleep deprivation remains unclear.